2012
DOI: 10.1002/adma.201202597
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Electron Spin Amplifier Based on Ga(In)NAs Alloys

Abstract: Efficient generation, maintaining, manipulation and detection of electron spin polarization and coherence at room-temperature (RT) in semiconductors is a prerequisite for the success of future semiconductor spintronics and quantum information technologies. [1][2][3][4][5] Potential spintronic devices are expected to be based on fundamental building blocks such as spin filters (or spin injectors or spin aligners), spin amplifiers and spin detectors. During the past decade spin filters and spin detectors have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Though the Overhauser field cannot be determined at RT simultaneously by optical polarization and ODMR, due to the instrumental limitation for the latter as described in the Methods section, this conclusion is supported by the following experimental findings. Firstly, the Ga i defects have been identified as the source of the defect-engineered spin-filtering/amplification effect that has led to strong spin polarization of conduction-band electrons 25,32 . From Hanle experiments, conduction-band electron spin polarization at RT is nearly entirely governed by the spin polarization of the electron localized at the defect 32,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the Overhauser field cannot be determined at RT simultaneously by optical polarization and ODMR, due to the instrumental limitation for the latter as described in the Methods section, this conclusion is supported by the following experimental findings. Firstly, the Ga i defects have been identified as the source of the defect-engineered spin-filtering/amplification effect that has led to strong spin polarization of conduction-band electrons 25,32 . From Hanle experiments, conduction-band electron spin polarization at RT is nearly entirely governed by the spin polarization of the electron localized at the defect 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the Ga i defects have been identified as the source of the defect-engineered spin-filtering/amplification effect that has led to strong spin polarization of conduction-band electrons 25,32 . From Hanle experiments, conduction-band electron spin polarization at RT is nearly entirely governed by the spin polarization of the electron localized at the defect 32,33 . It is, therefore, natural to expect that even a slight alternation in the spin polarization of the defect electron by the nuclear field induced by the DNP of the Ga i defect can result in a sizeable change in conduction-band electron spin polarization.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Moreover, strong spin-dependent recombination in these materials mediated by defects allows achieving a record-high electron spin polarization of up to 43% at room temperature (RT), which makes the Ga(In)NAs alloys an ideal materials system for innovative spin filters, spin detectors, amplifiers, and nuclear spin hyperpolarizers operational at RT. [13][14][15][16] Most recently, it was shown that GaNAs can be grown not only in planar but also in NW architecture, i.e., as a shell layer in GaAs/GaNAs core/shell structures. 17,18 This raises the prospect of combining advantages of this materials system with those offered by the one-dimensional (1D) NW architecture.…”
mentioning
confidence: 99%
“…Examples include its vital role in the spin blockade in semiconductor double quantum dots (QDs) due to the mixing of singlet/triplet states, 10,11 in the magnetoresistance effect observed in organic semiconductors, 15 in spin decoherence/relaxation in InAs QDs, 16 in hyperpolarization of local nuclear spins in semiconductors, 17 and in controlling electron spin coherence time of the P donor site in Si 6 and the nitrogen-vacancy center in diamond in the vicinity of 13 C nuclei spin bath. 7 In this work, we attempt to examine the role of HFI in the room-temperature (RT) defect-engineered spin-filtering effect, which has recently been demonstrated to be able to generate >40% spin polarization (P e ) of free electrons [18][19][20][21][22][23][24][25][26][27][28] and to amplify fast-modulating spin signals up to 2700% at RT 29 in Ga(In)NAs alloys. Since the key to the success of the defect-engineered spin-filtering is generation and maintaining of strong spin polarization of the electron localized at the spin-filtering defects, namely, Ga 2+ i interstitials, 18,[22][23][24][25] it is natural to ask whether HFI-induced spin mixing at such defects with a nonzero nuclear spin (I = 3/2 for its core Ga atom) will significantly affect the spin-filtering effect.…”
Section: Introductionmentioning
confidence: 99%